A study on the relationship of Emotional Intelligence and Adjustment of Secondary School Student of Papumpare District (AP) - Tage Ampa (Dera Natung Government College Research Journal)
The present study was carried out in Papumpare district of Arunachal Pradesh with an objective to examine the relationship between Emotional Intelligence and Adjustment of secondary school students in transition. The secondary level of education includes children between the age group of 14-18 years, the study was delimited to the sample of 2000 student of Class IX studying in Secondary schools in Papumpare District, Arunachal Pradesh. The result of the study suggests that there is a significant relationship between Emotional Intelligence and Adjustment of secondary school students in transition. The present study was also conducted to find out the relationship between Emotional Intelligence and Adjustment by taking into consideration of student’s emotional intelligence and adjustment score categorised as high, average and below average. The result reveals that there is significant relationship between Emotional Intelligence and Adjustment of secondary school students in transition under High category. There is significant relationship between Emotional Intelligence and Adjustment of secondary school students in transition under Average category. There is no significant relationship between Emotional Intelligence and Adjustment of secondary school students in transition under Below Average category.